Positividade micobacteriana entre os portadores de tuberculose ganglionar e pleural atendidos no Hospital Universitário João De Barros Barreto, Belém (Pa), 2001 a 2005 - NUNES, Mário Barbosa Guedes (2022)
Tuberculous pleuritis and lymphadenitis are the most common extrapulmonary clinical presentations of tuberculosis (TB). Immunosupressed patients, especially those HIV-infected, have increased risk for the development of extrapulmonay forms of TB, when compared to the general population. In the clinical practice, the diagnosis of this conditions is based on anamnesis, physical exam and finding of caseous granulomas at the microscopy of pleural or ganglia fragments. The identification of the etiologic agent is not even possible. Objctives: Verify the micobacterian positivity between Tuberculous pleuritis or lymphadenitis patients taken care at the Universitary Hospital João de Barros Barreto (HUJBB), since January 2001 to December 2005. Casuistry and Methods: We revised clinical sheets of all the patients taken care at HUJBB since January of 2001 to December of 2005 with diagnosis of ganglionar or pleural TB forms. Data collect was performed through standardized semi-closed questionnaire, contends demographics, clinical, laboratoriais variables, as well as histopathological findings. Thirty eight cases of tuberculous lymphadenitis and 98 of pleural TB had filled the inclusion criteria. Results: The average age was of 30,7 and 33,1 years old to the ganglionar and pleural forms, respectively. In both presentations was observed male predominance. Weight loss (20%), fever (15%) and cough (12%) had been the more frequent tuberculous lymphadenitis clinical manifestations. For the pleural form, fever (100%), chest pain (88,78%), cough (83,67%) and dispneia (69,39%) were the commonest signs and symptoms. Pulmonary form of TB was associated in 10,52% of the cases of the form to ganglionar and 16.32% of the pleural. AFB/micobactéria searching was made by bacterioscopia and/or culture, being positive in 28,12% and 5,1% for, respectively, ganglionar and pleural TB forms. HIV infection status did not determine difference in the occurrence of symptoms or the positivity for AFB/micobacteria. Conclusion: AFB/micobacteria positivity is relatively low between ganglionar and pleural tuberculous patients, giving to the histopathologic findings an important role in the diagnosis of these conditions.